(untitled) (The Pakistan Development Review, 2007)
The main purpose of this paper is to analyse the impact of trade reform on unemployment and social welfare in a Harris-Todaro (1970) economy with efficiency wage and capital mobility. The analysis shows that capital mobility plays an important role to influence the impact of trade reform on unemployment and social welfare. We find that trade reform raises urban unemployment and produces an ambiguous effect on social welfare when capital is perfectly mobile among the three sectors. However, such policy lowers unemployment and raises social welfare when capital is imperfectly mobile.